Pengaruh Brand Awareness, Consumer Trust, Percived Value, dan Word of Mouth terhadap Purchase Intention Konsumen Situs Belanja Online shopee di Yogyakarta - Erik Dian Pratama; Ambar Lukitaningsih; Nonik Kusuma Ningrum (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
This study aims to understand the impact of brand awareness, consumer trust, perceived value and word of mouth on purchase intention. The population used in this study were consumers of the online shopping site Shopee in Yogyakarta, the sampling technique used in this study was to use a purposive sample. Collecting data using a questionnaire on all consumers of the online shopping site Shopee in Yogyakarta. Data was taken using a questionnaire survey via Google Form using a Likert scale of 1 (strongly disagree) to 5 (strongly agree). Processed using multiple linear regression analysis. The results in this study state that brand awareness, perceived value, has no significant positive effect on purchase intention, while consumer trust, word of mouth, has a positive and relevant impact on purchase intention. Keywords: brand awareness; consumer trust; perceived value; word of mouth, purchase intention